2004
DOI: 10.5465/amle.2004.12436826
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Cultural Chameleon: Cultural Intelligence as a New Approach to Intercultural Training for the Global Manager

Abstract: The global economy and shifting political tides make the need for intercultural understanding and education obvious. Where historically the focus of intercultural training has been on preparing an individual to work in a new culture, today's organizations routinely ask managers to work in multinational environments and move from country to country. This challenge has created a strong debate about how to prepare managers for such challenging assignments. How ought people be assessed to understand their readines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
501
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(517 citation statements)
references
References 30 publications
8
501
0
8
Order By: Relevance
“…The alienation from the cultural mix of their classrooms, exposed by nine persons, evidences the urgent necessity of developing constructs to use to distinguish the aspects of the 'third space' and themselves. From this new perspective, the demands laid on developing an "intercultural mindset" (Hammer, 2009) can be met by introducing a new conceptual framework for EMI teacher training at URFU, including language repertoire growth and formation of cultural intelligence and metacognition as its critical aspect (Earley & Peterson, 2004). Thus, the EMI teachers armed with the adaptive strategies can take a proactive approach to potential cultural dilemmas and gain confidence in self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alienation from the cultural mix of their classrooms, exposed by nine persons, evidences the urgent necessity of developing constructs to use to distinguish the aspects of the 'third space' and themselves. From this new perspective, the demands laid on developing an "intercultural mindset" (Hammer, 2009) can be met by introducing a new conceptual framework for EMI teacher training at URFU, including language repertoire growth and formation of cultural intelligence and metacognition as its critical aspect (Earley & Peterson, 2004). Thus, the EMI teachers armed with the adaptive strategies can take a proactive approach to potential cultural dilemmas and gain confidence in self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural intelligence implies three fundamental elements: "metacognition and cognition (thinking, learning, and strategizing); motivation (efficacy and confidence, persistence, value congruence and affect for the new culture); and behavior (social mimicry and behavioral repertoire)" (Earley & Peterson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, effective intercultural adaptation and interaction cannot be achieved through automatic transferring of these skills. Earley and Peterson (2004), however, highlighted that a sufficient discussion of the cross-cultural context. Moon (2010) reported that EI could be effective when having contacts with people coming from various cultural backgrounds.…”
Section: Emotional Intelligence As a Moderator Agent Between Culturalmentioning
confidence: 99%
“…Kim et al (2006) maintained that through getting along with local individuals, emotional and informational support could contribute to the reduction of uncertainty in individuals and in an easier fashion obtain information concerning cultural norms and behaviors. Earley and Peterson (2004) and Earley and Ang (2003) stated that adaptation across cultures is not included in EI and it may be culturally specific. In other words, those individuals whose EI is high in their own native culture may not be capable of generalizing this ability across cultural contexts.…”
Section: Emotional Intelligence As a Moderator Agent Between Culturalmentioning
confidence: 99%
“…While international experiences and knowledge potentially can be helpful for students of all fields of study, they are especially important for business students as they often work across multiple borders and cultures (Earley & Peterson, 2004) from the first day of their employment. Regardless of one's opinion on the well-known discussion between Friedman and Florida on whether the world is flat (Friedman, 2005) -that means that countries such as India for example and their organizations are now on a (nearly) level playing field with the US, Europe, Japan and so on -or whether it is rather spiky (Florida, 2005) with economic clusters in certain areas of the world, it is safe to say that business students need to be in any case increasingly aware of the international business context.…”
Section: Introductionmentioning
confidence: 99%